2019
DOI: 10.3847/1538-4357/ab0b44
|View full text |Cite
|
Sign up to set email alerts
|

VEGAS: A VST Early-type GAlaxy Survey. IV. NGC 1533, IC 2038, and IC 2039: An Interacting Triplet in the Dorado Group

Abstract: This paper focuses on NGC 1533 and the pair IC 2038 and IC 2039 in Dorado a nearby, clumpy, still un-virialized group. We obtained their surface photometry from deep OmegaCAM@ESO-VST images in g and r bands. For NGC 1533, we map the surface brightness down to μ g  ≃ 30.11 mag arcsec−2 and μ r  ≃ 28.87 mag arcsec−2 and out to about 4 R e . … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 26 publications
(85 citation statements)
references
References 93 publications
9
76
0
Order By: Relevance
“…However, the accurate PSF deconvolution they applied indicates that the broadening takes effect at surface brightness levels fainter than μ r = 25 mag arcsec −2 (see their Figure 12). Results similar to Trujillo & Fliri () for the Gran Telescopio de Canarias+OSIRIS camera have been obtained by Spavone et al () and Cattapan et al () using VST + OmegaCam at ESO. We need to consider two facts.…”
Section: Observations and Reductionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the accurate PSF deconvolution they applied indicates that the broadening takes effect at surface brightness levels fainter than μ r = 25 mag arcsec −2 (see their Figure 12). Results similar to Trujillo & Fliri () for the Gran Telescopio de Canarias+OSIRIS camera have been obtained by Spavone et al () and Cattapan et al () using VST + OmegaCam at ESO. We need to consider two facts.…”
Section: Observations and Reductionsupporting
confidence: 81%
“…Very deep optical observations (e.g., Cattapan et al ; Spavone et al ; Trujillo & Fliri ) reaches surface brightness levels below 29–30 mag arcsec −2 in the r SDSS band. The detailed study by Trujillo & Fliri () showed that galaxies may be broadened in their outskirts by the PSF wings that scatter light.…”
Section: Observations and Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dorado group members morphology shows indeed the nearly ubiquitous presence of interaction signatures such as shells, asymmetries, tails (see e.g. Malin & Carter 1983;Cattapan et al 2019). Star-forming rings have been also revealed in several ETGs (Rampazzo et al 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Dorado CMD is described in Fig. 1 of Cattapan et al (2019). The red sequence of the group includes several ETGs.…”
Section: Introductionmentioning
confidence: 99%